Ensuring Legal Safeguards: Defendant Protection When Detained Beyond Time Limits: Perlindungan Hukum bagi Tersangka Saat Ditahan Melebihi Batas Waktu yang Ditentukan - Susilo, Rifka Annisa; Umar, Ahmad Riyadh (Indonesian Journal of Law and Economics Review, 2024)
Criminal law intricately intertwines with everyday life, regulating behaviors, subjects liable for punishment, and corresponding sanctions. This study employs normative research methods, analyzing literature and case studies to investigate violations within the criminal justice system, particularly concerning detention time limits. By scrutinizing legal statutes, theories, and precedents, this research unveils instances where defendants are deprived of their rights through unjustified extensions of detention beyond prescribed limits. The findings underscore the importance of upholding legal safeguards and the implications of disregarding procedural fairness in criminal proceedings. Highlights : The study elucidates the intersection of criminal law with everyday life, emphasizing regulations governing detention time limits. It underscores the significance of upholding procedural fairness in criminal proceedings to prevent legal injustices. Utilizing normative research methods, the research unveils instances of unjustified extensions of detention, highlighting the need for adherence to legal safeguards. Keywords: Criminal law, Detention time limits, Legal injustices, Procedural fairness, Normative research